Automated disposable small-scale bioreactor for high-throughput process development: implementation of the 24 bioreactor array. (June 2015) - Bareither, Rachel; Goldfeld, Marina; Kistler, Chris; Tait, Andrew; Bargh, Neil; Oakeshott, Robert; O'Neill, Kristin; Hoshan, Linda; Pollard, David
Aim: A disposable reactor system (250 ml scale) has now been developed into a fully automated 24 reactor array which includes process parameter monitoring and control, advanced feed strategies, automated event triggering, robotic arm liquid handling and sample storage.Results: Process and analytical comparability was shown for a range of Pichia, Escherichia coli and CHO cell-culture bioprocesses up to pilot and commercial scale. This established the system as a scale-down model for process development and characterization of large-scale industrial processes.Conclusion: This work demonstrated the ability of the automated system to accelerate process development by executing a single statistical design of experiments, with a wider range of parameters, up to 3–5-times faster than conventional approaches.